Internal vs. External Locus of Control: A Study of MSME Performance in Singaraja - Ariasih, Made Putri; Suarmanayasa, I Nengah (JUSTBEST Journal of Sustainable Business and Management, 2024)
MSMEs in Indonesia, including those in Singaraja, play an important role in the local economy, but often face challenges in improving their business performance. One of the psychological factors that can affect MSME performance is locus of control, which is divided into internal and external. This study aims to analyze the influence of internal and external locus of control on MSME business performance in Singaraja with a quantitative approach using multiple linear regression analysis. Data were collected from 62 MSMEs in Singaraja through a questionnaire measuring internal locus of control, external locus of control, and business performance. gacorqq The results of the analysis show that internal locus of control has a positive and significant effect on MSME business performance (regression coefficient = 0.354, p-value = 0.003), while external locus of control does not show a significant effect on business performance (regression coefficient = -0.056, p-value = 0.467). This study concludes that MSME owners with internal locus of control are more proactive in managing their businesses, which leads to better business performance. The practical implication of this research is the need for a program that develops internal locus of control for MSME owners to improve their business performance.